2020
DOI: 10.3390/antibiotics9060297
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids-Promising Antimicrobial Drugs or Intoxicants with Benefits?

Abstract: Novel antimicrobial drugs are urgently needed to counteract the increasing occurrence of bacterial resistance. Extracts of Cannabis sativa have been used for the treatment of several diseases since ancient times. However, its phytocannabinoid constituents are predominantly associated with psychotropic effects and medical applications far beyond the treatment of infections. It has been demonstrated that several cannabinoids show potent antimicrobial activity against primarily Gram-positive bacteria including me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 140 publications
(261 reference statements)
0
35
0
Order By: Relevance
“…Increasing evidence suggests that several diseases can be effectively treated by modulating endocannabinoids. [29][30][31][32][33] To determine the therapeutic potential of the endocannabinoid system, researchers have explored noncannabinoid receptor 1 (CB1) and non-CB2 receptor targets, such as MAGL. [33][34][35][36] As a key node in the endocannabinoid system, MAGL is primarily responsible for the activation of CB2 receptor and hydrolysis of 2AG.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that several diseases can be effectively treated by modulating endocannabinoids. [29][30][31][32][33] To determine the therapeutic potential of the endocannabinoid system, researchers have explored noncannabinoid receptor 1 (CB1) and non-CB2 receptor targets, such as MAGL. [33][34][35][36] As a key node in the endocannabinoid system, MAGL is primarily responsible for the activation of CB2 receptor and hydrolysis of 2AG.…”
Section: Discussionmentioning
confidence: 99%
“…Appendino et al investigated the antibacterial activity of five major cannabinoids and their analogs against a range of MDR S. aureus isolates [60]. It was found that cannabidiolic acid (CBDA) possesses good antimicrobial activity (MIC = 2 µg/mL, 8), which was further improved with omission of the carboxylate moiety (9). This has recently been verified by Martinenghi and co-workers, who observed that against several Gram-positive pathogens, CBD had MIC values in range of 1-2 µg/mL, compared with CBDA (2-4 µg/mL) [61].…”
Section: Structure-activity Relationships Of Cannabinoidsmentioning
confidence: 99%
“…Cannabis, or marijuana, is undoubtedly one of the most widely used illicit drugs [ 8 ]. It has a complex chemical composition that includes cannabinoids [ 9 ], which are a group of secondary metabolites, several of which are responsible for the psychotropic effects [ 10 , 11 ]. Metabolic fingerprinting of C. sativa unveiled more than 480 compounds, including many terpenes and approximately 180 cannabinoids [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinally, however, these compounds are recognised for their analgesic activity and thus medicinal applications in various neurological and musculoskeletal disorders [ 14 ]. Previous work has revealed that cannabinoids possess inhibitory activity against a range of bacteria and fungi [ 17 ], suggesting an antimicrobial potential for these compounds. Indeed, recent efforts have described the antibiotic potential of phytocannabinoids, with a particular focus on component cannabigerol (CBG) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%